Analysis of fall-related adverse events among older adults using the Japanese Adverse Drug Event Report (JADER) database - Haruna Hatahira; Shiori Hasegawa; Sayaka Sasaoka; Yamato Kato; Junko Abe; Yumi Motooka; Akiho Fukuda; Misa Naganuma; Satoshi Nakao; Ririka Mukai; Kazuyo Shimada; Kouseki Hirade; et al. (BMC, 2018)
Abstract Background Falls are a common but serious problem in older adults, and may lead to fractures and bleeding. As many factors, such as medication, aging, and comorbid diseases may simultaneously affect fall-related adverse events (AEs) in older adults, we evaluated the association between fall-related AEs and the use of medication, aging, and comorbid diseases using the Japanese Adverse Drug Event Report (JADER) database. Methods We analyzed reports of fall-related AEs associated with α-blockers, diuretics, calcium channel blockers, central nervous system (CNS)-active drugs (opioids, benzodiazepines, hypnotics and sedatives, non-selective monoamine reuptake inhibitors, and selective serotonin reuptake inhibitors (SSRI)) in the JADER database using the reporting odds ratio (ROR). For the definition of falls, we used the Preferred Terms of The Medical Dictionary for Regulatory Activities (MedDRA). We used the association rule mining technique to discover undetected associations, such as potential risk factors. Results The JADER database comprised 430,587 reports between April 2004 and November 2016. The RORs (95% CI) of α-blockers, diuretics, calcium channel blockers, opioids, benzodiazepines, hypnotics and sedatives, non-selective monoamine reuptake inhibitors, and SSRIs were 1.63 (1.27-2.09), 0.74 (0.63-0.86), 1.26 (1.15-1.38), 0.93 (0.80-1.07), 1.83 (1.68-2.01), 1.55 (1.12-2.14), 2.31 (1.82-2.95), and 2.86 (2.49-3.29), respectively. From the lift value in the association rule mining, the number of administered CNS-active drugs and patient age were associated with fall-related AEs. Furthermore, the scores of lift for patients with herpes zoster administered calcium channel blockers or benzodiazepines and patients with dementia administered benzodiazepines were high. Conclusion Our results suggest that the number of administered CNS-active drugs and patient age are both associated with fall-related AEs. We recommend that patients with herpes zoster treated with calcium channel blockers and benzodiazepines be closely monitored for fall-related AEs.